Development of a neonatal Göttingen Minipig model for dose precision in perinatal asphyxia: technical opportunities, challenges, and potential further steps - Stroe, Marina-Stefania; Van Bockstal, Lieselotte; Valenzuela, Allan; Ayuso, Miriam; Leys, Karen; Annaert, Pieter; Carpentier, Sebastien; Smits, Anne; Allegaert, Karel; Zeltner, Adrian; Mulder, Antonius; Van Ginneken, Chris; et al. (Frontiers in Pediatrics, 2023)
Animal models provide useful information on mechanisms in human disease conditions, but also on exploring (patho)physiological factors affecting pharmacokinetics, safety, and efficacy of drugs in development. For perinatal asphyxia (PA), a condition defined by oxygen deprivation in the perinatal period and possibly resulting in hypoxic ischemic encephalopathy (HIE) or even death, therapeutic hypothermia (TH) together with symptomatic drug therapy, is the standard approach to reduce death and permanent brain damage in these patients. The impact of the systemic hypoxia during PA and/or TH on drug disposition is largely unknown and an animal model can provide useful information on these covariates that cannot be assessed separately in patients. The conventional pig is proven to be a good translational model for PA, but pharmaceutical companies do not use it to develop new drug therapies. As the Göttingen Minipig is the commonly used pig strain in nonclinical drug development, the aim of this project was to develop this animal model for dose precision in PA. This experiment consisted of the instrumentation of 24 healthy male Göttingen Minipigs, within 24h of partus, weighing approximately 600g, to allow the mechanical ventilation and the multiple vascular catheters inserted for maintenance infusion, drug administration and blood sampling. After premedication and induction of anesthesia, an experimental protocol of hypoxia was performed, by decreasing the inspiratory oxygen fraction (FiO2) at 15%, using nitrogen gas. Blood gas analysis was used as an essential tool to evaluate oxygenation and to determine the duration of the systemic hypoxic insult to approximately one hour. The human clinical situation was mimicked for the first 24h after birth in case of PA, by administering four compounds (midazolam, phenobarbital, topiramate and fentanyl), frequently used in a neonatal intensive care unit (NICU). This project aimed to develop the first neonatal Göttingen Minipig model for dose precision in PA, allowing to separately study the effect of systemic hypoxia versus TH on drug disposition. Furthermore, this study showed that several techniques that were thought to be challenging or even impossible in these very small animals, such as endotracheal intubation and catheterization of several veins, are feasible by trained personnel.